2018
DOI: 10.1093/ije/dyy052
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal exposure to persistent organic pollutants and attention-deficit and hyperactivity disorder: a pooled analysis of seven European birth cohort studies

Abstract: In the largest study to date of 4437 children in seven European birth cohorts, we did not observe any association between either pre- or postnatal exposure (up to 24 months) to PCB-153, p-p´-DDE and HCB and the risk of ADHD before the age of 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 51 publications
0
13
0
3
Order By: Relevance
“…As noted above, the SDQ might not be sufficiently sensitive to specific behavioral ADHD-related problems. However, a lack of significant association with ADHD (defined based on a diagnosis reported in population-based registries or via questionnaires, including the SDQ and CBCL) was also reported in another study (Forns et al, 2018), in which the authors did not observe any significant association between either pre-or postnatal exposure (up to 24 months) to p,p′-DDE or hexachlorobenzene (HCB) and a diagnosis of ADHD, after adjusting for a number of variables (see Table 1). However, only one of the cohorts used relied on a specialist diagnosis recorded in population-based registries.…”
Section: Adhdmentioning
confidence: 77%
“…As noted above, the SDQ might not be sufficiently sensitive to specific behavioral ADHD-related problems. However, a lack of significant association with ADHD (defined based on a diagnosis reported in population-based registries or via questionnaires, including the SDQ and CBCL) was also reported in another study (Forns et al, 2018), in which the authors did not observe any significant association between either pre-or postnatal exposure (up to 24 months) to p,p′-DDE or hexachlorobenzene (HCB) and a diagnosis of ADHD, after adjusting for a number of variables (see Table 1). However, only one of the cohorts used relied on a specialist diagnosis recorded in population-based registries.…”
Section: Adhdmentioning
confidence: 77%
“…While there will be variability in exposure levels due to trends in exposure over time or regulatory policies, the ability to describe these temporal trends is a strength of the ECHO Program given that participant birth years span the early 1980s through present day. Overall, harmonization challenges can be overcome through thoughtful study design and statistical methods, as has been demonstrated in previous pooled studies of chemical exposures in US [ 232 234 ] and European [ 235 237 ] cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Depuis les années 2000, les études de cohortes et cas-témoins (Tableau 2) menées aux Etats-Unis, Japon, et Europe indiquent qu'une exposition prénatale aux PCB (PCB-DL, PCB-NDL, différents congénères) est associée à diverses altérations du neurodéveloppement chez les jeunes enfants et les enfants d'âge scolaire (7,8,(26)(27)(28)(29)(30)(31)(32)(33). Il s'agit d'altérations cognitives (concentration, attention, mémoire de travail verbale, visuelle, auditive), sensorimotrices, comportementales (impulsivité).…”
Section: Données éPidémiologiquesunclassified